An analysis of ASHA Facilitator Model: Assam, India - Nongdrenkhomba, Heikrujam Nongyai; Prasad, Banuru Muralidhara; Baishya, Achyut Chandra; Shome, Biraj Kanti (South East Asia Journal of Public Health, 2014)
Community Health Worker (CHW) models have evolved as a key community engagement strategy in healthcare. Accredited Social Health Activist (ASHA), is a CHW model, implemented to facilitate the process of community engagement in India under the National Rural Health Mission (NRHM). To support ASHAs, a supervisory structure is established, known as ASHA Facilitator. This structure is an amalgamation of various globally known models of supervision. Evidence suggests that the model of supervision is evolving and needs to have an understanding about interlink between community-program-health system. This study aims to analyze the programmatic and community role of ASHA Facilitators within the structure of existing models of supervision. The model of ASHA Facilitators encompasses the supervisory role to ensure service delivery and to monitor activities in relation to restorative, leadership and administrative support. A total of 291 ASHA Facilitators were selected for interview through a stratified random sample method from six districts of Assam, India representing six different regions/zones of the state. It was noted that programmatic roles were performed by ASHA volunteers as per guidelines; however, constrains were noticed in areas of authority and technicalities of program management. As a result, incentive-based tasks influenced the overall supportive supervision role of ASHA Facilitators. Non-incentivized roles/activities were performed on informal basis which were outside the mandate of program though essential (e.g. community resource generation activity). The current analysis recommends the strengthening of community health systems or community participatory supervisory systems in harmonization with community-program-health system through a more structured approach with a formal mechanism of supervision in order to meet the needs of community at large. DOI: http://dx.doi.org/10.3329/seajph.v3i2.20039 South East Asian Journal of Public Health Vol.3(2) 2013: 41-46